2019
DOI: 10.3390/nano9091299
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Genotoxicity of Polystyrene Nanoparticles on the Human Fibroblast Hs27 Cell Line

Abstract: Several studies have provided information on environmental nanoplastic particles/debris, but the in vitro cyto-genotoxicity is still insufficiently characterized. The aim of this study is to analyze the effects of polystyrene nanoparticles (PNPs) in the Hs27 cell line. The viability of Hs27 cells was determined following exposure at different time windows and PNP concentrations. The genotoxic effects of the PNPs were evaluated by the cytokinesis-block micronucleus (CBMN) assay after exposure to PNPs. We perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
83
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(87 citation statements)
references
References 54 publications
3
83
0
1
Order By: Relevance
“…The MPs also measurably induced pro-inflammatory cytokines IL-6 and TNF-α from human peripheral blood mononuclear cells (PBMCs), and increased histamine release from mast cell lines [118]. Poma and colleagues found that 100 nm PS NPs stimulated ROS production and induced genotoxic stress and DNA damage as measured with the cytokinesis-block micronucleus (CBMN) assay [119].…”
Section: Toxicity Of Mps/nps In Human Cellsmentioning
confidence: 99%
“…The MPs also measurably induced pro-inflammatory cytokines IL-6 and TNF-α from human peripheral blood mononuclear cells (PBMCs), and increased histamine release from mast cell lines [118]. Poma and colleagues found that 100 nm PS NPs stimulated ROS production and induced genotoxic stress and DNA damage as measured with the cytokinesis-block micronucleus (CBMN) assay [119].…”
Section: Toxicity Of Mps/nps In Human Cellsmentioning
confidence: 99%
“…Some recent in vitro studies have demonstrated the potential effects of MPs on human-derived cells [83][84][85]. These effects ranged from inflammation to DNA damage.…”
Section: Humanmentioning
confidence: 99%
“…These effects ranged from inflammation to DNA damage. Poma et al analyzed the effects of PS nanoparticles (PS-NPs) in the Hs27 cell line at different time windows and polymer nanoparticle (PNP) concentrations [83]. The authors adopted the cytokinesis-block micronucleus (CBMN) assay to evaluate the geno-Enyoh, et al | Microplastics exposure routes and toxicity EAHT toxic effects of the PS and the after exposure to PNPs.…”
Section: Humanmentioning
confidence: 99%
“…This issue contains mostly data from in vitro studies. In addition to classical cell lines such as hamster and human fibroblasts [ 1 , 2 ] or human lung cells [ 3 , 4 ], new models have been also used for investigating nanomaterials genotoxicity: ToxTracker reporter cell lines [ 5 ], human amniotic cells [ 6 ] and 3D HepG2 spheroids [ 7 ]. In this issue, three papers also deal with in vivo studies: on the plant Allium cepa [ 8 ], on the tadpoles of Xenopus laevis [ 9 ] and on rats [ 10 ].…”
mentioning
confidence: 99%
“…In this issue, three papers also deal with in vivo studies: on the plant Allium cepa [ 8 ], on the tadpoles of Xenopus laevis [ 9 ] and on rats [ 10 ]. Moreover, a broad range of nanomaterials have been tested, including plastic particles [ 2 ] that recently became of increasing concern for environmental and public health.…”
mentioning
confidence: 99%